Numerical analysis of temperature variations in chilled salmon packed in EPS boxes under dynamic temperature conditions - Helga Lilja Jónsdóttir 1991- (2018)
Thermally insulated packaging is an important factor in protecting fresh perishable foods from temperature abuse and reducing negative effects of insufficient temperature control in chill chains. Although the need for insulating packaging is high, plastic contamination is an environmental concern and there is clear motivation to reduce plastic use. The aim of this study is to experimentally and numerically compare two expanded polystyrene (EPS) boxes containing whole fresh Atlantic salmon. The boxes investigated are the original box currently in use, with a density of 23 kg/m3, and a new box with a reduced density of 21 kg/m3. In the experiment, the temperature was monitored at 7 locations inside six boxes during a 6 hour storage at an ambient temperature of around 20°C. The experimental results were used to validate a three-dimensional time-dependant heat transfer model, which was developed using ANSYS FLUENT, a computational fluid dynamics (CFD) software. A satisfactory agreement between the numerical and experimental results was achieved with an overall mean absolute error of 0.6°C and 0.5°C for the original and lighter boxes, respectively. A low difference in remaining shelf life (∆RSL) at 0°C between the simulation and experiment was also obtained. The model was further developed to simulate the temperature evolution in boxes with thinner walls under the same ambient temperatures. Results suggest that decreasing the density of the EPS is a feasible option to reduce plastic use, as the difference in remaining shelf life between the two box types was minimal. Einangrandi umbúðir gegna mikilvægu hlutverki til að vernda fersk matvæli og draga úr neikvæðum áhrifum óæskilegra hitasveiflna sem verða í kælikeðjum. Þrátt fyrir mikla þörf á vel einangrandi umbúðum er plastmengun stórt umhverfisvandamál og þar af leiðandi hvatning til að draga úr notkun plasts stórt atriði. Markmið þessarar ritgerðar er að bera saman tvo frauðplastkassa (EPS) sem innihalda heila ferska eldislaxa með tilraun og líkanagerð. Kassarnir ...